Antipsychotic-Related Hypothermia: Five New Cases - Zonnenberg, Cherryl; Bueno-de-Mesquita, Jolien M.; Ramlal, Dharmindredew; Blom, Jan Dirk (Frontiers in Psychiatry, 2019)
Background: Hypothermia is a potentially fatal adverse effect of antipsychotic drug (APD) use. With only 69 cases described in the literature, the condition is considered rare. Methods: We describe five new cases, in which we estimated the role of clozapine, haloperidol, olanzapine, penfluridol, risperidone, and zuclopentixol with the aid of two structured assessment tools. Results: In addition to APD use, all five patients described by us had been exposed to one or more additional predisposing factors for hypothermia. Therefore, with the aid of the assessment tools, the causal role of APDs was considered ‘possible’ in four cases of moderate hypothermia, and ‘doubtful’ in the remaining one of mild hypothermia. Conclusion: Although the best way to detect APD-related hypothermia is measuring the body temperature for a duration of at least 7-10 days after the start (or a dose increase) of APDs, the use of assessment tools to identify additional predisposing factors for hypothermia and establish their causal relationship with APD use would seem to be valuable for clinical decision-making (i.e., whether or not to discontinue APD use). Further research is needed to obtain reliable prevalence figures for APD-related hypothermia and its consequences, preferably in relation with physiological changes in body temperature.